2001
DOI: 10.1046/j.1365-8711.2001.04182.x
|View full text |Cite
|
Sign up to set email alerts
|

On the excitation mechanism in roAp stars

Abstract: We investigate a model for the excitation of high‐order oscillations in roAp stars. In this model we assume that the strong concentration of magnetic field about the magnetic poles is enough to suppress convection. Thus the model considered is composed of two polar regions, in which convection is presumed to be suppressed totally, and an equatorial region, where the convection is unaffected. This model is generated by building pairs of locally spherically symmetrical equilibria to represent the polar and equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
231
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(241 citation statements)
references
References 36 publications
(42 reference statements)
10
231
0
Order By: Relevance
“…It is clear that all the radial modes in the roAp frequency regime (1 mHz < v < 3 mHz) are damped. The results are similar to those found by Balmforth et al (2001) in their equatorial model. We also see an increased damping near the acoustic cut-off frequency.…”
Section: The Damping Ratessupporting
confidence: 91%
See 2 more Smart Citations
“…It is clear that all the radial modes in the roAp frequency regime (1 mHz < v < 3 mHz) are damped. The results are similar to those found by Balmforth et al (2001) in their equatorial model. We also see an increased damping near the acoustic cut-off frequency.…”
Section: The Damping Ratessupporting
confidence: 91%
“…In particular, Balmforth et al (2001) demonstrated that the interplay between magnetism and convection in roAp stars can lead to excitation of some modes through driving in the polar regions. However, we expect that the atmospheric behaviour found in the present calculations will nonetheless be representative of more realistic models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since their discovery by Kurtz (1982), only 61 of these objects have been identified (see Smalley et al 2015 for a catalogue). The pulsations are high-overtone pressure modes (p modes) thought to be driven by the κ-mechanism acting in the H i ionisation zone (Balmforth et al 2001). However, Cunha et al (2013) ⋆ Based on service observations made with the WHT operated on the island of La Palma by the Isaac Newton Group in the Spanish Observatorio del Roque de los Muchachos of the Instituto de Astrofísica de Canarias.…”
Section: Introductionmentioning
confidence: 99%
“…The reason may be due to the presence of a magnetic field in this case. Extension of this kind of studies have been discussed for roAp stars by Balmforth et al 2001.…”
Section: The Stellar Casementioning
confidence: 99%